PENGARUH TINGKAT KEPUASAN PENGUNJUNG TERHADAP KINERJA PELAYANAN PETUGAS TAMAN MINI INDONESIA INDAH JAKARTA - Arief, Andi Moh. Rifiyan (SOROT, 2011)
Research done with descriptive method korelasioner and assisted by the way ofdistributing questionnaires to vositors who next data procesing using a likert.From the discussion that there is then obtained correlation value (r) of 0,8576, which meanthere is a very strong/ high among the service performance of officers of the level of visitorsatisfaction in this area. Coefficient of determination of 73,55%. This can be said thatperformance of service by Taman Mini Indonesia Indah influenced by the level of satisfactionof visitors and the rest equal to 24,45%, Taman Mini Indonesia Indah officer performance isinfluenced by other factors such as who was has not studied the work environment and motivation.